Federal Repositories: Comparative Advantage in Open Access? - Alvin Hutchinson (Issues in Science and Technology Librarianship)
The article offers the author's views on the issue of access to federally funded science through federal repository libraries in the U.S. The impact of the policy encouraging deposit of publications resulting from National Institutes of Health-funded projects into the PubMed Central digital repository is discussed. Examples of other government bodies that create peer-reviewed science every year are highlighted.